1999
DOI: 10.1034/j.1399-0039.1999.540109.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA class II alleles with different subgroups of diabetes mellitus in Eastern India identify different associations with IDDM and malnutrition‐related diabetes

Abstract: Genetic studies of Malnutrition related diabetes are few. We have analyzed HLA class II gene polymorphism in different types of diabetes mellitus patients from Cuttack in Eastern India. Patients with insulin-dependent diabetes mellitus (IDDM), non-insulin-dependent diabetes mellitus (NIDDM) and malnutrition-related diabetes mellitus (MRDM), which is subdivided into protein-deficient diabetes mellitus (PDDM) and fibrocalculous pancreatic diabetes (FCPD), were studied and their associations with autoantibody mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
5
33
1
Order By: Relevance
“…6 Other case-control studies have also reported associations between the HLA and FCPD but not with the same HLA-DQB1 allele. 8,9 For example in eastern Indian subjects from Cuttack an association was found between FCPD and HLA-DQ9 (A* 0201-B*0303); this was different to that found in T1DM and protein deficiency diabetes mellitus. 8 Despite these reported HLA associations there is little evidence to support FCPD being an autoimmune disease.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…6 Other case-control studies have also reported associations between the HLA and FCPD but not with the same HLA-DQB1 allele. 8,9 For example in eastern Indian subjects from Cuttack an association was found between FCPD and HLA-DQ9 (A* 0201-B*0303); this was different to that found in T1DM and protein deficiency diabetes mellitus. 8 Despite these reported HLA associations there is little evidence to support FCPD being an autoimmune disease.…”
Section: Introductionmentioning
confidence: 69%
“…8,9 For example in eastern Indian subjects from Cuttack an association was found between FCPD and HLA-DQ9 (A* 0201-B*0303); this was different to that found in T1DM and protein deficiency diabetes mellitus. 8 Despite these reported HLA associations there is little evidence to support FCPD being an autoimmune disease. For example, there is no increase in antibodies to islet cells or glutamic acid decarboxylase compared to a control population, 10 and the clinical picture is very different from T1DM.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations